Characteristics of Liquid Sugar from Cassava Flour Using Gelatinization, Liquefaction and Enzymatic Saccharification (amyloglucosidase and α-amylase) Processes - Agustina, Tika; Elsyana, Vida; Alvita, Livia Rhea; Ramandani, Adityas Agung; Purnani, Mawar Siti (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
Domestic sugar production is still insufficient to satisfy the national demand for sugar, and production costs are expensive. One of the ingredients that can be used to make liquid sugar is starch. This study aims to determine the response of the resulting reduced sugar by optimizing the substrate concentration, liquefaction, and saccharification time. The method used of Box Behnken Design (BBD) with combinations of 20, 30, and 40% substrate concentrations, liquefaction times of 20, 40, and 60 min, and saccharification times of 20, 40, and 60 min. The characteristics of cassava flour, such as moisture (9.208 ± 0.068%), ash (0.987 ± 0.001%), fiber (2.187 ± 0.033%), and starch (79.876 ± 0.000%), were satisfied on SNI 01-2905-1992. Liquid sugar made from cassava flour reduced the sugar content by 28.299 ± 0.101%. The optimal conditions were 40% substrate concentration, 60 min liquefaction time, and 60 min saccharification time. The characteristics of the validation liquid sugar are in accordance with the specifications for the quality requirements of SNI 01-2978-1992 in the form of moisture content, ash content, and reducing sugar of 5.194 ± 0.003%, 0.996 ± 0.000%, and 29.668 ± 0.761%, respectively. These results highlight the effectiveness of optimizing substrate concentration, liquefaction time, and saccharification time in producing high-quality liquid sugar from cassava flour. This optimization addresses the domestic demand for sugar. It provides a cost-effective solution by utilizing cassava flour, thereby supporting the local agricultural economy and potentially reducing reliance on imported sugar.